MONETARY SYSTEM OF THE REPUBLIC OF UZBEKISTAN AND ITS ELEMENTS: https://doi.org/10.5281/zenodo.16736676 - Bozorboyev , Diyorbek (Science technology&Digital finance, 2025)
This article covers the modern monetary system of the Republic of Uzbekistan and its main structural elements. The monetary system is an integral part of the economy of any state, in which such aspects as the circulation, emission, exchange rate of the national currency, cash and non-cash settlements, international payments, as well as the balance of supply and demand for money occupy an important place. When Uzbekistan gained independence, it began to pursue an independent monetary policy through the introduction of the national currency, the sum. The article also analyzes the role of the central bank in controlling the money supply, ways to ensure the stability of the national currency, the importance of anti-inflation measures.